2013
DOI: 10.1039/c3cp50437a
|View full text |Cite
|
Sign up to set email alerts
|

Improving charge collection in Escherichia coli–carbon electrode devices with conjugated oligoelectrolytes

Abstract: It is important to tailor biotic-abiotic interfaces in order to maximize the utility of bioelectronic devices such as microbial fuel cells (MFCs), electrochemical sensors and bioelectrosynthetic systems. The efficiency of electron-equivalent extraction (or injection) across such biotic-abiotic interfaces is dependent on the choice of the microbe and the conductive electrode material. In this contribution, we show that spontaneous intercalation of a conjugated oligoelectrolyte, namely 4,4'-bis(4'-(N,N-bis(6''-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 40 publications
2
83
1
Order By: Relevance
“…21,27 In contrast to previous reports, the IM remains primarily intact under our experimental conditions. 9 Since the conditions described herein closely mimic that used in MFCs, it is unlikely that the increased extracellular electron transfer (EET) in MFCs is due to cell lysis.…”
Section: 8contrasting
confidence: 53%
“…21,27 In contrast to previous reports, the IM remains primarily intact under our experimental conditions. 9 Since the conditions described herein closely mimic that used in MFCs, it is unlikely that the increased extracellular electron transfer (EET) in MFCs is due to cell lysis.…”
Section: 8contrasting
confidence: 53%
“…DSSNϩ, 1,4-bis(4Љ-(N,N-bis(6ЉЉ-(N,N,N-trimethylammonium)hexyl)amino)-styryl)benzene tetraiodide (DSBNϩ), and 1,4-bis(4Љ-(N,N-bis(6ЉЉ-(N,N,N-trimethylammonium)hexyl)amino)-styryl)-2,3,5,6 tetrafluorobenzene tetraiodide (4F-DSBNϩ) were synthesized as reported previously (2,11). The MIMs used in this study were selected because their biotechnological potential had been demonstrated previously in bioelectrochemical systems and because interesting interactions with microbial cells have been documented (1,3,10).…”
Section: Methodsmentioning
confidence: 99%
“…E. coli K-12 cells were incubated for 15 min in the dark with 5 and 64 M DSSNϩ, 5 M DSBNϩ, and 5 M 4F-DSBNϩ, while E. faecalis cells were treated with 1 M (each) DSSNϩ, DSBN, and 4F-DSBNϩ in the dark for 15 min. Treatment concentrations were selected to be close to but not above their corresponding MIC values (Table 2), with the exception of DSSNϩ, where values were selected to correspond to biotechnologically useful concentrations (1) and to be close to the MIC of DSSNϩ in E. coli, enabling the comparison of the toxic effects of all MIMs in both E. coli K-12 and E. faecalis using TEM. Following MIM treatment, cells were washed twice with PBS and resuspended to a final OD 600 of 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations